Assessment of 'Blue carbon' in sediment of Indian mangrove (Avicennia Officinalis) in selected locations of Vembanadad lake ecosystem in Kerala - Aarathy, G S (Academy of Climate Change Education and Research, 2018)
The present investigation, focused on the estimation of the sediment pool of the blue carbon stocks of the mangrove species Avicennia officinalis (Indian Mangrove) in selected locations of Vembanad lake. Sediment core samples were collected in post monsoon (October – November 2017) and pre monsoon (February – March 2018). The treatments included ‘aged’, ‘recent’, ‘healthy’ and ‘degraded’ mangroves of the selected species and ‘control’ without mangroves. Sediment core samples up to 30 cm depth with 10 cm interval were subjected to standard laboratory and statistical analytical procedures. The cumulative stock of blue carbon in sediment ranged from 6.00 to 139.96 Mg ha -1 in post monsoon and 2.00 to 84.58 Mg ha -1 in pre monsoon. The treatments differed significantly in the cumulative stock of blue carbon in sedimen (p < 0.05), highest seen in ‘healthy’ at 0-30 cm depth in both seasons. Highly significant difference was observed between ‘healthy’ and ‘degraded’, ‘healthy’ having more stock in both seasons. These two treatments differed significantly for layer wise blue carbon in sediment also in both seasons, higher content being seen in ‘healthy’ and there was no significant variation among depths. The range of layer wise blue carbon in sediment, considering all treatments was 0.06 to 0.56 g cm-3 in post monsoon and 0.02 to 0.35 g cm-3 in pre monsoon. Significant difference among treatments was observed at 0-10 cm depth for layer wise blue carbon in two seasons together, and no significant variation was found in sub surface (10-20 cm and 20-30 cm) depth. Spatial maps were prepared for the cumulative stock of blue carbon and layer wise blue carbon in sediment during post monsoon and pre monsoon seasons. The cumulative stock and layer wise blue carbon were higher in post monsoon. Depth wise increase was seen in layer wise blue carbon in post monsoon, though they were not statistically significant. Layer wise blue carbon was significantly correlated with total organic carbon and organic matter (p < 0.01) positively and with C/N ratio in the sediment (p < 0.05). The study suggests total organic carbon and C/N ratio as possible predictive indicators of blue carbon in sediment, with further investigation.